Examining the relationship between green marketing and green purchasing intentions: UNIQLO customers in Jabodetabek - Kevin, Kevin; Ginting, Ari Mulianta (Institute of Computer Science (IOCS), 2025)
This research examines the impact of green marketing on green purchasing intentions among UNIQLO customers in Jabodetabek. With growing environmental awareness, fashion companies like UNIQLO are adopting eco-friendly marketing to attract conscious consumers. Key factors explored include environmental sensitivity, attitudes toward green products, and green product quality, which influence purchase intentions. Data will be collected from UNIQLO customers in Jabodetabek and analyzed to identify the relationships between these variables. The research aims to provide actionable insights for UNIQLO to develop sustainable marketing strategies and understand how consumers' perceptions of eco-friendly products are shaped. Additionally, the study offers practical recommendations for companies aiming to enhance the adoption of green products